Modeling Failures and Repair Times of the Rifle Famae Sg 542-1 Applying Hierarchical Coloured Petri Nets [Modelación de Las Fallas y Tiempo de Reparación del Fusil Famae Sg 542-1 Aplicando Redes de Petri Coloreadas Jerárquicas] - Reyes-Campana, H (Universidad de Tarapaca, 2022)
This paper presents the modelling and simulation of a complex system applying the hierarchical coloured Petri nets method to represent the failure and repair processes, as well as obtaining statistical data indicating its performance. The simulation was performed on the model of a mechanical system characterized by the FAMAE SG 542-1 war rifle, commonly used in the Chilean Army, through the CPN Tools and Python software representing how components perform of operation of this weapon. This behaviour is recorded through both software, obtaining the simulation data so that it will be possible to predict the condition of a component and the system in the future to generate corresponding action plans. © 2022, Universidad de Tarapaca. All rights reserved.